1992
DOI: 10.1182/blood.v80.1.91.bloodjournal80191
|View full text |Cite
|
Sign up to set email alerts
|

Separation of hematopoietic stem cells into two populations and their characterization

Abstract: Two populations of hematopoietic stem cells (HSC) in mouse bone marrow (BM) are defined on the basis of the presence or absence of interleukin- 3 (IL-3) receptor-associated antigen (IL-3RAA). HSC were purified by depletion of mature lymphoid-lineage cells followed by collection of the low-density fraction and sorting of wheat germ agglutinin-binding (WGA+) cells using a fluorescein-activated cell sorter. WGA+ cells were further separated into two populations (IL-3RAA+/WGA+ and IL-3RAA- /WGA+) by a monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We have found that NS cells in mouse and monkey BM have low density, a high affinity (more cell surface receptor) to wheat germ agglutinin [14,24], and the receptor for interleukin 3 [16]. From these results, it is anticipated that NS cells are hematopoietic progenitors committed to myeloid lineage [30,31]. In the present study, of cells that lack lineage markers, those with relatively low density (BM Fr.…”
Section: Discussionmentioning
confidence: 71%
“…We have found that NS cells in mouse and monkey BM have low density, a high affinity (more cell surface receptor) to wheat germ agglutinin [14,24], and the receptor for interleukin 3 [16]. From these results, it is anticipated that NS cells are hematopoietic progenitors committed to myeloid lineage [30,31]. In the present study, of cells that lack lineage markers, those with relatively low density (BM Fr.…”
Section: Discussionmentioning
confidence: 71%
“…We have previously shown that IL-3Rprogenitor cells are more primitive than IL-3R + cells [4]. In the present study, we examined the expression of IL-6R on CD71 -H-2 high cells.…”
Section: Discussionmentioning
confidence: 83%
“…An effective method of purifying pluripotent hemopoietic stem cells (P-HSC) would contribute not only to clarifying the mechanism behind hemopoietic differentiation and selfrenewal of P-HSC, but also to the use of P-HSC in bone marrow transplantation (BMT). Until now, a number of laboratories have reported different purification procedures, including those based on physical characteristics (size and cell density), negative selection to remove lineage-committed cells and positive selection using various markers [1][2][3][4][5][6][7][8][9]. Visser et al purified stem cells using density centrifugation followed by positive selection, utilizing both binding ability to wheat germ agglutinin (WGA) and anti-H-2KAb with a cell sorter [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, more committed progenitors, responsive to either IL-3 or GM-CSF, were not affected by TNF-o~ (2). In this context, another study has recently demonstrated that IL-3 receptor-negative progenitors are more primitive than those expressing IL-3 receptors (18). Finally, these in vitro observations, which identify TNF-ot as an important molecule for the recruitment of early hematopoietic progen-itors are supported by the demonstration of the radioprotective effect of TNF-ol in vivo (19).…”
Section: Tnf-ot Recruits a Population Of Ceils With Both Monocytic mentioning
confidence: 98%